Circular Economy Practices in the Electrical and Electronic Equipment Sector in the European Union - Ionela-Corina Chersan; Mirela Paunescu; Elena-Mirela Nichita; Valentin Florentin Dumitru; Cristina Lidia Manea (Amfiteatru Economic, 2023)
Our research objective is to investigate the circular economy practices implemented by manufacturers in the electric appliance sector. The research methodology was mixed, selecting relevant fragments from the nonfinancial reporting of a sample of entities in the European Union and following the whole process, from the conception of the product to the end of its life. The results indicate that the companies analysed take similar actions. Therefore, the companies' efforts are focused not only on finding solutions for equipment manufacturing based on a circular model (increasing the use of recycled or easily recyclable materials, reducing consumption or recycling more efficiently) but also on changing the way the consumer uses the products (for instance, by finding solutions to recover equipment components and reuse them, by reducing consumption, or even by recycling the generated waste). The study contributes to improving the knowledge of the actions taken to implement a circular business model by companies in a sector that consumes large amounts of resources and generates significant waste, such as the one analysed. The results highlight the intentions and progress made by companies producing electric appliances in their transition to the circular business model.
Keywords: P48; Q01; Q57; 330; circular economy practices; electrical and electronic equipment; electric appliances; extended product value business model; sustainability reporting